C(sp3)–H functionalization of methyl azaarenes: a calcium-catalyzed facile synthesis of (E)-2-styryl azaarenes and 2-aryl-1, 3-bisazaarenes. Issue 43 (21st October 2015) - Yaragorla, Srinivasarao; Singh, Garima; Dada, Ravikrishna
Graphical abstract: Abstract: Alkaline earth (Ca 2+ ) catalyzed sp 3 C–H functionalization of methyl azaarenes for the synthesis of biologically important ( E )-2-styryl azaarenes, 2-aryl-1, 3-bisazaarenes and 3, 3-bisazaarenyl indolinones has been described. Initially methyl azaarenes react with aryl aldehydes to give β-hydroxy derivatives, which undergo Ca(II) catalyzed thermodynamic elimination to give the styryl azaarenes in a single step. Similarly it may undergo SN 1 reaction to give 2-aryl-1, 3-bisazaarenes and 3, 3-bisazaarenyl indolinones (if isatin used as the electrophile). This green synthetic methodology enjoys the simple reaction procedures, solvent free conditions, step economy, substrate diversity and high yields of the products in short time.